Por el placer de la vida (2021)
It is with great emotion that we present this booklet as a result of arduous research work by the team from the Antonio Nariño University, Santamaría Foundation, and the EAFIT University, within the framework of the project “Senses built around the use and non-use of condoms in relation to HIV in key populations, transgender women and men who have sex with men (MSM) in the city of Cali and Medellín”. Throughout this process, for two years (2019-2021) we had the opportunity to get closer to the feelings of the population of men who have sex with men and that of Trans Women regarding sexuality, while they shared their experiences and anecdotes. . Through interviews, focus groups and spaces for formal and informal conversation, we were able to recognize that sexuality is lived, felt and enjoyed in different ways; that it is not just one and that there are so many expressions, feelings, behaviors, experiences, and practices, as people in the world.